Peran Guru Pendidikan Agama Kristen dalam Membina Moral Siswa dari Latar Belakang Keluarga Fatherless - Ruhut Parningotan Tambunan; Theresa Dian Christi; Yonatan Alex Arifianto (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2026)
The increasing number of students from fatherless families affects students’ moral formation, character, and spiritual development. The absence of a father figure reduces role modeling, supervision, and guidance, thereby increasing vulnerability to identity crises, deviant behavior, and weak Christian moral development. Christian Religious Education teachers play a strategic role in fostering students’ morality through exemplary behavior, spiritual guidance, and restorative educational relationships. This study aims to analyze the role of Christian Religious Education teachers in holistically fostering the morality of students from fatherless families. The study employs a descriptive qualitative approach using literature review and content analysis of relevant scientific literature. The results indicate that teachers serve as moral guides, spiritual mentors, and role models of Christian character through pastoral guidance, reflective learning, and educational relationships that strengthen students’ identity, integrity, and moral resilience. This study proposes the Restorative Christian Moral Formation (RCMF) Model, which integrates relational acceptance, spiritual mentoring, biblical character formation, collaborative care, and transformative moral practice as a framework for restorative moral formation. This model contributes both conceptually and practically to strengthening the moral formation of students from fatherless families within the context of contemporary Christian Religious Education. Abstrak Meningkatnya jumlah siswa dari keluarga fatherless memengaruhi pembentukan moral, karakter, dan perkembangan spiritual peserta didik. Ketiadaan figur ayah mengurangi keteladanan, pengawasan, serta pendampingan sehingga meningkatkan kerentanan terhadap krisis identitas, perilaku menyimpang, dan lemahnya perkembangan moral Kristiani. Guru Pendidikan Agama Kristen memiliki peran strategis membina moral siswa melalui keteladanan, pendampingan spiritual, dan relasi edukatif yang restoratif. Penelitian ini bertujuan menganalisis peran Guru Pendidikan Agama Kristen dalam membina moral siswa berlatar belakang keluarga fatherless secara holistik. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka dan analisis isi terhadap berbagai literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa guru berperan sebagai pembimbing moral, mentor spiritual, dan teladan karakter Kristiani melalui pendampingan pastoral, pembelajaran reflektif, serta relasi edukatif yang memperkuat identitas, integritas, dan ketahanan moral siswa. Penelitian menawarkan Model Restorative Christian Moral Formation (RCMF) yang mengintegrasikan relational acceptance, spiritual mentoring, biblical character formation, collaborative care, dan transformative moral practice sebagai kerangka pembinaan moral restoratif. Model ini berkontribusi secara konseptual dan praktis dalam memperkuat pembinaan moral siswa fatherless pada konteks Pendidikan Agama Kristen kontemporer.